Quick crocheted accessories : 3 skeins or less - Zientara, Sharon (Interweave, 2015)
In Quick Crocheted Accessories, author Sharon Zientara has curated a collection of crocheted projects that make use of one, two, or three skeins of yarn, allowing for both color play and larger projects. Crocheters will enjoy quick crochet projects including scarves and shawls, hats, fingerless mitts and mittens, and slippers and socks!--